PENGGUNAAN BIOKOMPOS DAN BIOAKTIVATOR FORMULASI BUTIRAN YANG MENGANDUNG TRICHODERMA SPP. UNTUK MENINGKATKAN HASIL KEDELAI DI TANAH ENTISOL - Burhanudin Burhanudin (Unisda Journal of Mathematics and Computer Science (UJMC), 2016)
One of the biggest problem on soybean production in Indonesia is low it's productivity (1,174 tons/ha). Indonesia is one of the biggest soybean import country from overseas 1,7 million tons in year of 2013. There are a number of factors causing low productivity of soybean in Indonesia including : (1) limited harvest areas, (2) declining soil fertility, (3) decreasing agricultural land due to other users, (4) decreasing interest of farmers in soybean due to low benefit comparing with other crops. Therefore it is important to study The use of biocompost and bioactivator in a granule formulation containing Trichoderma spp to enhance yield of soybean in tropopsament. The aim of the study was to improve the production and productivity of soybean. This experiment was conducted in the field using a factorial experiment design. As the main plots (PU) was biocompost consist of 4 levels (b0) control (No biocompost added), (b1) 5 tons/ha of biocompost, (b2) 10 tons/ha of biocompost and (b3) 15 tons/ha of biocompost and sub-plots (AP) was a bio-activator consist of (f0) without the application of bioactivator, (f1) 0,3 tons/ha of bioactivator, (f2) 0.7 tons/ha of bioactivator and (f3) 1,1 tons/ha of bioactivator. The results showed that: (1) the application biocompost 10 tons/ha resulted of 2,863 tons/ha yield of soybean and the lowest yield resulted from the control treatment 1,709 tons/ha; (2) application of bioaktiavtor of 1,1 tons/ha resulted 2,764 tons/ha soybean yield and the lowest yield was resulted from the the control without the application of bio-activator was about 1,859 tons/ha. In addition the application of biocompost increased soybean yield by 23,65% while the application of bioactivator increased yield by 23,54% bio-action. In conclustion application of optimum level of both biocompost and bioactivator incresed soybean yield by more than 23%, however from farmers" benefit cost analysis, the application of bioactivator is much more beneficial for farmer than application of biocompost.